Dynamics of disability and work in Canada - Umut Oguzoglu (Institute for the Study of Labor (IZA), 2012)
Canadian disability policy has come a long way in the past century. However, in contrast with the evidence that disability is not permanent for most, current disability support programs still carry the old static view of permanent disability. By employing a dynamic panel data model of labour force participation, the findings of this paper suggest that labour force exposure is crucial for better return-to-work outcomes for persons with a disability. Without labour force exposure, the effect of a temporary disability is prolonged and participation efforts of the disabled community are slowed down.
Keywords: J14; J21; C23; 330; disability; labour force participation; dynamic panel data models; Behindertenpolitik; Behinderte Arbeitskräfte; Erwerbstätigkeit; Berufliche Integration; Kanada